Taking stock: A critical review of recent research on monetary policy transmission mechanism - Zakaria Bahari (Penerbit Universiti Kebangsaan Malaysia, 2003)
The classical and more recent literatures on the transmission of monetary policy on economic performance offer a wide range of issues. Among the issues are; the potential roles of financial intermediaries in economic growth, the transmission of monetary policy to real variables, and the choices of financial indicators. The last two issues, in providing financial services, the financial intermediaries contribute to the economic growth by transmitting monetary policy to real variables as well as becoming important financial indicators. Several studies find that the debt financing is important to firms, particularly for financing investment of new project and to expand the current business activities. The question arises on how the monetary policy affect the firm behaviour? We will show that there are two complementary ways of explaining about how firm might be influenced by the changes of monetary policy. First, the balance sheet channel is identified whereby the condition of firm’s balance sheets is a source of output fluctuations. Second, the bank lending channel that stresses the ability of monetary policy to regulate the pool of funds available to the bank-dependent firms. This paper provides the investigation of those issue